Improvement of the mechanisms of land use of farming Enterprises in Ukraine : ст. - Lypchuk, V. et. al. (Stepan Gzhytskyi National University of Veterinary Medicine and Biotechnologies, 2019)
Nowadays, Ukraine experiences intensive use of land resources and a high level of economic employment of land areas. In 2017, agricultural lands constituted 68.7 % of the total area of Ukraine, and the area of plowed land occupied 78.4 % [12, p. 65]. Scientists report about poor efficiency of application of organizational and economic mechanisms of rational land use, imperfect management of use, protection and reclamation of land resources. It causes deterioration of the land fund quality [7, p. 149–150]. Land is the main asset in agriculture and a key element of production potential of farming enterprises [10, p. 80]. However, position of farming enterprises in the organizational system of agrarian production directly depends on the possibility to become a participant of market transactions concerning land parcels. In that aspect, development of lease relations, being capable to supply necessary resource parameters of economic subjects, particularly concerning land, is a crucial factor [9, p. 14]. Creation of production potential of farming enterprises is a complicated and continuous process, which expects a balanced and proportional combination of the required labor, land and material resources [5, p. 97]. Thus, land supply is a factor, which determines other resources, on one hand, and a result of production factors interaction, on the other hand. The mentioned issues confirm timeliness of the topic of the research. It needs substantiation of scientific and practical approaches concerning land use of farming enterprises in Ukraine to secure their competitive advantage.
Keywords: farms; land use; землекористування